Association between triglyceride-glucose index and hypertension in adults with cancer from NHANES 2005–2018: a cross-sectional study - Gangping Li; Di Zhang; Minghui Li; Fangfang Yuan; Yongqi Wang; Yuewen Fu (BMC Cancer)
Abstract Background Insulin resistance (IR) is linked to hypertension development.The triglyceride-glucose (TyG) index is a proposed alternative biochemical marker for IR. This study aimed to explore the relationship between TyG and hypertension in adults with cancer. Methods A cross-sectional study was conducted involving 1,222 cancer adults patients from the NHANES dataset (2005–2018). Demographics, medical history, lifestyle factors, and lab tests were assessed. Multivariable logistic regression, subgroup analysis, and smooth curve-fitting techniques were used. Results Among 1,222 eligible participants, 775 (56.29%) had hypertension. When TyG was assessed as a continuous variable, higher TyG levels were significantly associated with increased hypertension prevalence (OR, 1.51; 95% CI, 1.09–2.11; p = 0.015) after adjusting for covariates. When TyG was analyzed as quartiles, compared to individuals with lower TyG Q1 (7.0–8.3), the adjusted OR values for TyG and hypertension in Q2 (8.3–8.7), Q3 (8.7–9.1), and Q4 (9.1–10.7) were 1.32 (95% CI: 0.85–2.06, p = 0.022), 1.63 (95% CI: 1.01–2.64, p = 0.043), and 1.68 (95% CI: 1.09–2.84, p = 0.041), respectively. The data were stratified by age, sex, marital status, education level, and family income. Stratified analysis revealed no significant interactions among subgroups (all p-Values > 0.05). Analysis using restricted cubic splines(RCS) suggested a linear relationship between TyG and hypertension in adults with cancer. Conclusions Higher TyG levels are associated with an increased risk of hypertension in adults with cancer.